Deficit Budget and Economic Growth in Nepal - Kadel, Suren Babu (Management Dynamics, 2021)
This article attempts to identify the relationship between budget deficit and economic growth in Nepal. A deficit budget is associated with the role of government in the economy. On employing the ARDL bounds test on the data set from 1990 to 2020, it is found that there is a long-run relationship between the budget deficit and economic growth. The bound test and error correction term specify a long-run relationship between the Nepalese economy’s budget deficit and economic growth. According to the empirical study, the budget deficit significantly impacts real GDP, a proxy for economic growth.